Validity and Readability of E-Worksheet Based on Education Sustainable Development Assisted by Digital Climate Map on Global Warming Material - Islamiyah, Ahla Nurul; Lestari, Nurita Apridiana (IPF: Inovasi Pendidikan Fisika, 2025)
Global warming has a significant impact on the environment, with the earth's temperature continuing to rise due to human activities that produce carbon emissions, such as burning fossil fuels and deforestation. Sustainable education (ESD) is key in addressing this issue, through the implementation of curriculum and learning methods based on sustainability values. This research aims to develop physics learning tools in the form of E-Worksheet digital map-based to support students' understanding of the issue of global warming. The utilization of technology in E-Worksheet allows flexible access, real-time, and environmentally friendly, in line with ESD principles. This research uses the ADDIE model R&D design which is focused until the Develop stage to develop ESD-based Physics E-Worksheet learning media on global warming and climate change material. Qualitative data was obtained from the responses of validators and students, while quantitative data came from the Likert scale results in the validation and readability tests. The product validity results showed an average of 85% (valid with minor revisions), while the readability test obtained an average of 88.98% (very good). This media is declared suitable for use in learning because it is practical, supports sustainability education, and increases students' knowledge and awareness of environmental issues. The limitation of the research lies in the focus on the development stage, so further research is needed to test the effectiveness and implementation of the product.